General approach to prepare polymers bearing pendant isocyanate groups. Issue 32 (4th August 2020) - Navarro, Rodrigo; García, Carolina; Rodríguez-Hernández, Juan; Elvira, Carlos; Marcos-Fernández, Angel; Gallardo, Alberto; Reinecke, Helmut
Abstract : A versatile synthetic approach for the easy preparation, under smooth reaction conditions, of diverse classes of linear polymers bearing aliphatic or aromatic isocyanate groups in the side chains is described. Abstract : A versatile synthetic approach for the easy preparation, under smooth reaction conditions, of diverse classes of linear polymers bearing aliphatic or aromatic isocyanate groups in the side chains is described. The procedure consists in the transformation of primary amine groups present in the polymer into isocyanates using equimolar amounts of diphosgene or triphosgene and a soluble tertiary amine as the acid scavenger. The transformation of all amine groups takes place quasi-simultaneously and instantaneously as shown by the invariability of the chain length of the polymer and the absence of crosslinked products. The number of isocyanate groups per molecule that can be achieved by this approach corresponds to the number of primary amine groups of the starting polymer and is up to three orders of magnitude higher than in any other non-crosslinked molecule described so far. The isocyanate functionalized polymers can be used to anchor a large variety of molecules to the polymer chains. The approach is in detail demonstrated with poly(vinyl chloride) (PVC) carrying aromatic amine groups but has also been confirmed by using a number of other polymer types bearing both aromatic and aliphatic primary amines. Furthermore, it has been used to prepare a novel low molecular weight compound, tris(2-cyanatoethyl)amine.